1998
DOI: 10.1074/jbc.273.46.30568
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Expression of a Water-soluble Chlorophyll Protein, a Putative Carrier of Chlorophyll Molecules in Cauliflower

Abstract: A water-soluble chlorophyll protein (WSCP) 1 in Brassicaceae plants has been purified from Lepidium virginicum (1), Brassica nigra (wild mustard) (1), Brassica oleracea var. botrys (cauliflower) (2, 3), Brassica oleracea var. gemmifera (Brussels sprouts) (4), and Brassica napus var.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
127
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(139 citation statements)
references
References 40 publications
11
127
0
1
Order By: Relevance
“…Furthermore, the recombinant apo-WSCP was able to remove Chl from the thylakoid membrane in vitro and organize the tetrameric WSCPChl complex (3). The absorption spectrum of the reconstituted complex is very similar to that of the native WSCP-Chl complex purified from fresh leaves (1,3).…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…Furthermore, the recombinant apo-WSCP was able to remove Chl from the thylakoid membrane in vitro and organize the tetrameric WSCPChl complex (3). The absorption spectrum of the reconstituted complex is very similar to that of the native WSCP-Chl complex purified from fresh leaves (1,3).…”
mentioning
confidence: 55%
“…Botrys) and Chl or its derivatives showed that the central Mg 2ϩ ion and the phytyl tail of Chl were essential for protein-pigment binding and tetrameric assembly, respectively (1). Furthermore, the recombinant apo-WSCP was able to remove Chl from the thylakoid membrane in vitro and organize the tetrameric WSCPChl complex (3). The absorption spectrum of the reconstituted complex is very similar to that of the native WSCP-Chl complex purified from fresh leaves (1,3).…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…[18][19][20][21][22][23] Furthermore, various molecular genetic analyses on recombinant Class II WSCPs have been performed. 18,[20][21][22][23][24][25][26][27][28][29][30][31][32] On the other hand, CaWSCP is the only gene encoding a Class I WSCP identified to date and few studies on the molecular genetics of the protein have been performed thus far. 33,34) Identification of novel genes encoding Class I WSCPs is essential for understanding the molecular diversity of the protein.…”
mentioning
confidence: 99%